The use of Chinese-English code-switching on Facebook among Malaysians / Shao Yajing - Shao, Yajing (2013)
Code-switching is a kind of strategy bilingual or multilingual speakers use in their daily interaction where they alternate between two or more languages in a certain context or conversation. Facebook, a kind of new computer-mediated communication (CMC), is one of the favorite social networking websites with more than 900 million users all over the world (Joshi & Rutledge, 2011, p. 63). This study hopes to fill the gap on how code-switching is used on the social networking website by undergraduate students who are studying in a public university in Malaysia, especially for those who study Chinese as their program so that textbooks on learning English or Chinese can be developed for future use. The main objective of this study is to analyze the types and functions of Chinese-English code-switching and English-Chinese code-switching instances used on Facebook by 13 Malaysian Chinese undergraduate bilinguals who are in their second and final year studying in the Chinese Program in a public university of Malaysia. Two theoretical frameworks are adopted in this study which are Poplack’s (1980) code-switching types and Appel and Muysken’s (2005) functions of code-switching. The data consisted of statuses posted by participants from October, 2012 to December, 2012 on Facebook. Through three months, this study finds that Chinese is the dominant language on Facebook among bilingual participants, and Chinese-English code-switching instance is highly used as compared to English-Chinese code-switching instance. There are some differences between Chinese-English code-switching and English-Chinese code-switching forms, which are intra-sentential switching is highly used among Chinese-English code-switching instances, whereas inter-sentential switching is frequently used among English-Chinese code-switching instances. Referential function, expressive function, phatic function and metalinguistic function are various functions used by participants on Facebook among Chinese-English code-switching and English-Chinese code-switching instances.